Metaverse-Enhanced Virtual Reality UsingAvatar forUniversity Campus - Fakhar Jabran; Tehmina Sheharyar; Halima Sadia (Spectrum of Engineering Sciences, 2025)
With Metaverses and Virtual reality in its initial ages andeveninitsinitial ages it is doing wonders for humanity. One of themostimportant things it contributes to is in education. This thesisexplores the possibility to get to know how Metaverse-EducationUniversity Campus, with the main focus of avatar-based orientationprograms in VR environment. This study focuses on howeffectivethis technology is alongside how it can improve the educational possibilities. We applied many methods to this approach; weusedureal engine 4 to make the 3d Virtual Environment for theVRorientation session. Unreal Engine was again used to createAvatarsand the VR capabilities. The findings are expected toprovideinsights into the benefits and challenges of implementingVR-based orientation programs and offer recommendations foreducational institutions considering adopting Metaversetechnologies. This study contributes to the literatureoneducational technologies in the world already publishedandgives a platform to institutions such as universities and collegestoprovide a starting blueprint to implement VR-based educationintotheir campuses. Keywords: VR, Avatars, educational technologies, Metaverse